Digital entrepreneurial intention among private Technical and Vocational Education (TVET) students - Vejaratnam, Navaratnam; Paramasivam, Theepa; Mustakim, Siti Salina (Human Resource Management Academic Research Society, 2019)
The study aims to determine the intention of Technical and Vocational Education (TVET) students to become digital entrepreneurs. To achieve this purpose, Ajzen theory of Planned Behaviour was applied. This quantitative study was conducted through distribution of survey questionnaires which involving 185 participants from one of the private TVET institution located in Kajang. The respondents were determined based on simple random sampling technique. SPSS version 23 was applied to conduct different tests such as multiple regression and descriptive statistics. The result showed that students were highly intended to become digital entrepreneur. Specifically, the knowledge gain from classes had shaped the student’s positive attitude and more self-confident to be an entrepreneur. The contribution of this study also expected to help the management to produce more digital entrepreneurs in era of Industry 4.0.